Chernobyl still affects the environment of Greece: Recent measurements of 137Cs in soil cores from Grevena–Trikala area - Ioannidis, I.; Mertzimekis, T. J.; Godelitsas, A.; Stamoulis, K. C.; Ioannides, K. G. (HNPS Advances in Nuclear Physics, 2019)
Cores to a depth of 20 cm from surface were collected from Central Greece to study the 137Cs concentration and mobility in soils from the most afflicted areas by the Chernobyl Accident. As we are approaching a time almost equal to one halflife of radiocesium from the Chernobyl accident, new data can be proven extremely useful for assessing the present status.